2014
DOI: 10.1080/10615806.2014.955018
|View full text |Cite
|
Sign up to set email alerts
|

Resource loss, self-efficacy, and family support predict posttraumatic stress symptoms: a 3-year study of earthquake survivors

Abstract: Receiving social support from relatives shortly after an earthquake was found to be an important coping resource, as it alleviated the association between resource loss and the severity of posttraumatic stress response, compensated for deficits of self-efficacy, and enabled self-efficacy, which was in turn associated with more adaptive adjustment 3 years after the earthquake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 39 publications
3
18
0
2
Order By: Relevance
“…In addition, Benight and colleagues examined individuals’ acute disaster responses (1–4 months post-disaster) and medium-range disaster recovery (8–12 months); thus, their period of examination differs from our period. Our findings of a lack of relationship with recovery are, however, similar to the findings of Warner, Gutierrez-Dona [ 13 ]. These authors found that posttraumatic stress reactions 3 years after an earthquake were not significantly related to concurrent GSE after posttraumatic stress reactions at 1 to 6 months were taken into consideration.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, Benight and colleagues examined individuals’ acute disaster responses (1–4 months post-disaster) and medium-range disaster recovery (8–12 months); thus, their period of examination differs from our period. Our findings of a lack of relationship with recovery are, however, similar to the findings of Warner, Gutierrez-Dona [ 13 ]. These authors found that posttraumatic stress reactions 3 years after an earthquake were not significantly related to concurrent GSE after posttraumatic stress reactions at 1 to 6 months were taken into consideration.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in a study conducted after a natural disaster, they found a similar relationship between CSE and later distress, as assessed by a measure of global psychological distress [ 12 ]. A recently published study [ 13 ] found that GSE was not significantly related to posttraumatic stress reactions 3 years post-earthquake when posttraumatic stress reactions 1–6 months post-disaster were taken into account. Unfortunately, GSE was assessed at follow-up but not prior to the period of change.…”
Section: Introductionmentioning
confidence: 99%
“…However, the above studies have been pertinent to adults, and the majority of the studies have ignored the impact of other personality traits (e.g., psychoticism). It has not yet been determined what role personality traits play in PTSD or depression symptoms among children after a catastrophe when primary personality traits are included and other risk factors are controlled 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The few existing longitudinal studies have produced mixed findings concerning the temporal relationship between self-efficacy and posttraumatic stress symptoms. Some longitudinal studies of natural disaster survivors found self-efficacy to be related to lower levels of posttraumatic stress symptoms longitudinally (Benight et al, 1999; Benight and Harper, 2002) or to moderate the effect of social support on stress symptoms (Warner et al, 2015). However, we previously found self-efficacy to be related only to concurrent posttraumatic stress symptoms (Johansen et al, 2007) and to be unrelated to posttraumatic stress symptoms beyond 6 months post-disaster (Nygaard et al, 2016).…”
Section: Introductionmentioning
confidence: 99%